Contribution of the Waste Management on Job Creation and Anthropo-Social Circular Economy - Hakizimana, Lucien; Gómez, Jorge Marx; Ntaganda, Laurent (Journal of Organizational Psychology, 2025)
Waste management remains a global challenge, particularly in Rwanda’s rural areas, where inadequate systems lead to environmental degradation, health risks, and economic losses. This study focused on improving waste management in Byumba through Gicumbi Agriculture Production Market (GAPM) Ltd. Data was collected from 14 GAPM staff and beneficiaries using questionnaires and analyzed both quantitatively and qualitatively. Findings revealed that GAPM Ltd employs various waste management techniques, including landfill (100%), re-use (100%), recycling (100%), disposal (71.2%), composting (64.3%), and recovery (57.1%). These methods contribute to a circular economy by creating jobs (100%), protecting the environment (100%), conserving resources (85.7%), improving social well-being and health (78.6%), generating economic benefits (71.4%), and fostering community engagement (57.1%). The study confirms that GAPM Ltd’s waste management strategies significantly enhance sustainability. It recommends that the government strengthen awareness campaigns to educate communities on proper waste management and its crucial role in socio-economic development, ensuring long-term environmental protection and economic growth in rural areas.